Perubahan Pembuatan Post-Flight Information Di Penerbangan - Br.Sibarani, Ilona Gisela; Amir, Elfi; Sugih Arti, Endang (Jurnal Bisnis dan Operasi Penerbangan, 2025)
Post-flight information is information regarding the condition of the aircraft, information on the next flight, accident or loss reports (if any) which can be used for analysis, learning and decision making, which is reported after flight operations. The research method used is a qualitative research method where the researcher conducts a study of group culture in natural conditions through observation and interviews. Post-flight information plays an important role because it contains information needed for flight safety.